Individual and organizational antecedents of trait mindfulness - TURGUT, TÜLAY; KALAFATOĞLU, YAPRAK (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
Previous research on the antecedents of mindfulness is scarce. This study examines the individual and contextual antecedents, specifically ethical climate and goal orientation, of trait mindfulness. Data for this study came from 302 white-collar employees working in Istanbul who completed cross-sectional questionnaires on ethical climate, goal orientation, and mindfulness. First, it was found that caring climate, which refers to organizations that consider the wellness of its workforce, positively predicted employees' trait mindfulness. Second, goal orientation was significantly associated with trait mindfulness. Mastery and performance-approach orientations both predicted positively to trait mindfulness with mastery orientation the strongest predictor. In contrast, a performance-avoidance orientation predicted negatively to trait mindfulness. As a caring climate predicts to employees' mindfulness, it is recommended that organizations create a workplace where employees perceive themselves as family members, with an emphasis on teamwork, participation, and intrinsic motivation.
Keywords: Mindfulness; goal orientation; ethical climate; ETHICAL CLIMATE; GOAL ORIENTATION; DISPOSITIONAL MINDFULNESS; SELF-REGULATION; WORK CLIMATE; MOTIVATION; PERFORMANCE; SATISFACTION; CLASSROOM; BEHAVIOR